Telomere Length and Telomerase Activity in Foetal Membranes from Term and Spontaneous Preterm Births - Colatto, Brunna Nepomuceno; de Souza, Isabela Fiorentino; Schinke, Laura Aparecida Antonio; Noda-Nicolau, Nathalia Mayumi [UNESP]; da Silva, Marcia Guimarães [UNESP]; Morceli, Glilciane; Menon, Ramkumar; Polettini, Jossimara (Springer Nature, 2020)
The reduction of telomere length, the protective cap structures of chromosomes, is one of the biomarkers of senescence (a mechanism of ageing), and ageing of foetal gestational tissues is associated with both term and preterm parturition. A mechanism regulating telomere length is the activity of telomerase, an enzyme that adds telomere fragments during DNA replication and cell division; however, its role in regulating telomere length is not well studied in gestational tissues. The objective of this study is to correlate telomere length and telomerase activity in foetal membranes from term and spontaneous preterm births. Foetal membrane samples were collected from pregnant women experiencing term labour (TL), term not in labour (TNL), preterm premature rupture of membranes (pPROM) and spontaneous preterm labour (PTL) with intact membranes (n = 20/group). Telomere length and telomerase activity were analyzed by relative quantification (T/S), real-time PCR and PCR-based fluorometric detection, respectively. Data were analyzed by ANOVA or the Kruskal-Wallis test. Demographic variables were not statistically different among the groups. Foetal membranes from the TL group showed telomere length reduction compared with those from the others (p < 0.0002). Telomerase activity did not change in foetal membranes irrespective of pregnancy outcome. Telomere shortening in foetal membranes is suggestive of senescence associated with triggering of labour at term; however, this is likely independent of telomerase activity, while prematurity may be associated with senescence, but due to other mechanisms than telomere length reduction in foetal membranes.
Keywords: Gestational complications; Pregnancy; Senescence